Subterranean Cities : The World beneath Paris and London, 1800-1945 - Pike, David L. (David Lawrence), 1963- (Book collections on Project MUSE., 2005)
"The underground has been a dominant image of modern life since the late eighteenth century. A site of crisis, fascination, and hidden truth, the underground is a space at once more immediate and more threatening than the ordinary world above. In 'Subterranean Cities', David L. Pike explores the representation of underground space in the nineteenth and early twentieth centuries, a period during which technology and heavy industry transformed urban life. The metropolis had long been considered a moral underworld of iniquity and dissolution. As the complex drainage systems, underground railways, utility tunnels, and storage vaults of the modern cityscape superseded the countryside of caverns and mines as the principal location of actual subterranean spaces, ancient and modern converged in a mythic space that was nevertheless rooted in the everyday life of the contemporary city. Writers and artists from Felix Nadar and Charles Baudelaire to Charles Dickens and Alice Meynell, Gustave Dore and Victor Hugo, George Gissing and Emile Zola, and Jules Verne and H.G. Wells integrated images of the urban underworld into their portrayals of the anatomy of modern society. Illustrated with photographs, movie stills, prints, engravings, paintings, cartoons, maps, and drawings of actual and imagined urban spaces, Subterranean Cities documents the emergence of a novel space in the subterranean obsessions and anxieties within nineteenth-century urban culture. Chapters on the subways, sewers, and cemeteries of Paris and London provide a detailed analysis of these competing centers of urban modernity. A concluding chapter considers the enduring influence of these spaces on urban culture at the turn of the twenty-first century."--